KONTRIBUSI GAYA KEPEMIMPINAN KEPALA MADRASAH TERHADAP EFEKTIVITAS KERJA GURU MADRASAH IBTIDAIYAH - Saeful Hasanudin (Pascasarjana Unviersitas Majalengka, 2020)
The research was motivated by the low work effectiveness of Madrasah Ibtidaiyah teachers in Sukahaji Majalengka District, which allegedly was caused by the leadership style of the madrasah principal that was not suitable for the environment. This study aims to determine: a) the leadership style of the principal of the madrasah; b) teacher work effectiveness; c) the magnitude of the contribution of the principal's leadership style to the effectiveness of teacher work. This research uses a quantitative approach with descriptive analysis design and verification. The method used is a survey method, with the main data collection tool in the form of a questionnaire distributed to 53 respondents. The data obtained were analyzed using a parametric statistical approach. The results showed that descriptively the leadership style of the principal and the effectiveness of the work of the teachers were in good condition. Verificatively, the leadership style of the madrasah principal contributes to the effectiveness of teacher work. In conclusion, the leadership style of madrasah principals has a significant contribution to teacher work effectiveness